Наука і практика як чинник успішності підготовки фахівців обліково-аналітичного спрямування - Кіндрацька, Л. М. (Видавництво Львівської політехніки, 2014)
Обґрунтовано авторське бачення щодо посилення наукової та практичної складової процесу викладання обліково-аналітичних дисциплін у вищій школі. Подано можливі варіанти підвищення наукової компоненти знань студентів, нові підходи до складання програм навчальних дисциплін, підготовки методичного забезпечення навчального процесу та оновленого формату підручників. Overview scientific component values and its dynamic growth in the formation of the modern educational process in the preparation of accounting and analytical experts.Argued the growth needs of the scientific component of the prevailing professional competence in this area of knowledge. Grounded author vision in relation to strengthening of scientific and practical constituent of teaching process registration-analytical disciplines at higher school. The possible variants of increase of scientific are presented components of knowledges of students, new going near drafting of the programs of educational disciplines, preparation of the methodical providing of educational process and renewed format of textbooks. There are a number of arguments supporting the need for the isolation problem interdisciplinary approach to the study of many disciplines. It is noted that it is quite a complex issue, in which the solution should provide a step by step gradual transition of competencies acquired by one discipline to the competencies that they have acquired by the students in another discipline. Directions which can integrate accounting with the social and natural sciences to form the desired information on the economic, social and environmental sustainability vectors. It is proved that an analytical system acquires the status of a kind of pyramid bases of decision making by managers at all levels, which are at the top of finances. As a phenomenon they reflect the cash flows of economic agents, which are characterized by volume, direction and time.
Science and practice as a factor success training specialists accounting and analytical targeting
Keywords: навчальний процес; викладання; обліково-аналітичні дисципліни; наукова компонента; компетенції; міждисциплінарний підхід; learning process; teaching; accounting and analytical disciplines; scientific component; competence; interdisciplinary approach